The Effectiveness of the Combination of Seaweed (Gracillaria sp.), Blood Shells (Anadara granosa), and Zeolite as Biofilter in the Reduction of Heavy Metal Copper (Cu) - Ivan Achmadi; Boedi Setya; Annur Ahadi (Universitas Airlangga, 2020)
Heavy metal Cu is an essential heavy metal that is a heavy metal needed to stimulate the activity of enzymes during metabolism. Cu metal has a tendency to be toxic as long as its presence has exceeded the threshold value. The metal-contaminated water environment has the potential to affect the surrounding environment. The purpose of this study was to determine the effectiveness of Cu heavy metal reduction by using a combination of seaweed biofilter (Gracillaria sp.), Blood shells (Anadara granosa), and zeolites. This study uses a combination of biofilter between seaweed (Gracillaria sp.) And blood shells (Anadara granosa) with different concentrations in each treatment. The results showed the use of the right biofilter combination can reduce levels of heavy metals Cu. The initial content of heavy metal Cu is 1 mg / L to 0.119 mg / L, the best combination composition on P4.